Pengaruh Air Cucian Beras terhadap Pertumbuhan Jumlah Daun pada Tanaman Bayam (Amaranthus spp.) - Bahari, Apriadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Spinach (Amaranthus spp.) is a plant that is commonly grown for its leaves as green vegetables. This plant originates from tropical America, but is now spread throughout the world. This study aims to determine the effect of rice washing water on the growth of the number of spinach leaves (Amaranthus spp.). The design used in this study was a Completely Randomized Design (CRD), consisting of 3 treatments with 9 replications, namely: P1 (750 ml of rice washing water + 750 ml of plain water); P2 75% (1125 ml of rice washing water + 375 ml of plain water); and P3 100% (1500 rice water). The variables observed were the number of spinach leaves (Amaranthus spp.). The results of this study indicate that in the P1 treatment, the number of spinach leaves (Amaranthus spp.) was obtained in succession, namely: 50 strands, 62 strands, 63 strands, 63 strands, 86 strands, 97 strands, 105 strands, and 113 strands. While in the P2 treatment, the number of spinach leaves (Amaranthus spp.) was obtained in succession, namely: 46 strands, 65 strands, 77 strands, 71 strands, 91 strands, 98 strands, 102 strands, and 118 strands. In the P3 treatment, the number of spinach leaves (Amaranthus spp.) from the 1st to the 8th week were consecutively: 48 strands, 62 strands, 66 strands, 71 strands, 90 strands, 104 strands, 119 strands, and 143 strands, with an average observation result on the number of spinach leaves (Amaranthus spp.) of 87 strands.